Identification of novel antifungal agents: antimicrobial evaluation, SAR, ADME–Tox and molecular docking studies of a series of imidazole derivatives - Btissam Bouchal (BMC Chemistry, 2019)
Abstract Thirty-four imidazole-based compounds synthesized by one-pot catalytic method were evaluated for their antifungal and antibacterial activities against several fungal and bacterial strains. None of the compounds had antibacterial activity. Interestingly, compounds 1, 2, 3, 10 and 15 displayed a strong antifungal activity against all the tested fungal species, while compounds 5, 7, 9, 11, 21 and 27 showed a moderate antifungal activity. To better understand the biological activity of the most active compounds ADME–Tox and molecular docking studies were carried out. Interestingly, compounds 1, 2, 3, 7, 10 and 15 showed excellent bioavailability. In addition, compounds 1, 2 and 3, exhibited good toxicity profiles. Docking studies of the two most active compounds 2 (IC50 of 95 ± 7.07 μM) and 10 (IC50 of 235 ± 7.07 μM) suggested that they might act by inhibiting the fungal lanosterol 14α-demethylase. Therefore, these novel antifungal agents merit further characterization for the development of new antifungal therapeutics.